To what extent is the Cooperative Learn Work Method beneficial to improve the written production of tenth grade students? (2016)
ABSTRACT: The Action Research Proposal (ARP) showed how through the Cooperative Learning Work Method (CLWM), tenth grade students reinforced their English learning writing skills with constructing simple sentences. (ARP) showed how students could apply the CLWM to reinforce their English learning in writing skills with the simple sentences. The main objective: to involve students more in the English class, through individual and group activities, and feel more motivation to learn not just individually, but as a group too. This implementation had observations for a group of thirty-four, tenth grade students with writing sessions, Evaluate English learning process were: survey to Cooperating Teacher and two questionnaires to students. The second stage was to implement an action plan over two school terms.